2022
DOI: 10.3389/fonc.2022.883197
|View full text |Cite
|
Sign up to set email alerts
|

Construction of ceRNA Networks Associated With CD8 T Cells in Breast Cancer

Abstract: BackgroundThe infiltration of CD8 T cells is usually linked to a favorable prognosis and may predict the therapeutic response of breast cancer patients to immunotherapy. The purpose of this research is to investigate the competing endogenous RNA (ceRNA) network correlated with the infiltration of CD8 T cells.MethodsBased on expression profiles, CD8 T cell abundances for each breast cancer (BC) patient were inferred using the bioinformatic method by immune markers and expression profiles. We were able to extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…was just the opposite. Combined with relevant studies [33,37] , we believe that the signal regulation involved by lnc-AL031775 and lnc-AC005332.4 may play a protective role in the cancer prognosis. We used ROC and c-index curves to validate the prognostic accuracy of the model.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…was just the opposite. Combined with relevant studies [33,37] , we believe that the signal regulation involved by lnc-AL031775 and lnc-AC005332.4 may play a protective role in the cancer prognosis. We used ROC and c-index curves to validate the prognostic accuracy of the model.…”
Section: Discussionmentioning
confidence: 53%
“…It was also involved in the competing endogenous RNA network correlated with the in ltration of CD8 T cells. It may predict the therapeutic response of breast cancer and osteosarcoma patients to immunotherapy [37,38] . Lnc-KLF7-IT1 is a novel lncRNA identi ed as a cuproptosis-related lncRNA in our study that has not been previously reported, which can help us to nd a new target for cancer therapy mainly.…”
Section: Discussionmentioning
confidence: 99%
“…Although MIR9-3HG was highly expressed in cervical cancer and could regulate apoptosis in cervical cancer cells by affecting the mitochondria-mediated apoptosis pathway ( 42 ), a study has shown that MIR9-3HG is a protective gene ( 39 ). Meanwhile, AC005332.4 has also been reported in colorectal cancer ( 43 ), cervical cancer ( 44 ), breast cancer ( 45 ), and osteosarcoma ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…reported in colorectal cancer (43), cervical cancer (44), breast cancer (45), and osteosarcoma (46).…”
Section: Discussionmentioning
confidence: 99%
“…GAS5 reportedly promotes wound healing by activating the HIF1A/ VEGF pathway [43]. Dysregulation of the lncRNAs MBNL1-AS1, CCDC18-AS1, LINC01290, MIR29B2CHG, and PSMB8-AS1 has been observed in many cancers [44][45][46][47][48]. NF-κB signaling is activated during DMD pathogenesis and leads to infammation and muscle degeneration [49].…”
Section: Discussionmentioning
confidence: 99%